Politeness: A Socio- Pragmatic Study (Journal of the College of Languages (JCL), 2014)
The most influential theory of ‘Politeness’ was formulated in 1978 and revised in 1987 by Brown and Levinson. ‘Politeness’, which represents the interlocutors’ desire to be pleasant to each other through a positive manner of addressing, was claimed to be a universal phenomenon. The gist of the theory is the intention to mitigate ‘Face’ threats carried by certain ‘Face’ threatening acts towards others. ‘Politeness Theory’ is based on the concept that interlocutors have ‘Face’ (i.e., self and public – image) which they consciously project, try to protect and to preserve. The theory holds that various politeness strategies are used to protect the ‘Face’ of others when addressing them. This theory proposes that there is a positive and a negative ‘Face’. The former reflects the desire to be approved by others, while the latter avoids being imposed on. Therefore, the use of the proposed ‘Politeness Strategies’ differ according to ‘Face’. However, neither the ‘Face’ is a set phenomenon nor the strategies are applicable to all cultures, since culture – bound aspects may vary. These indicate shortcomings in the theory, since the ‘Face’ acceptability vary from one person to another and social relations, attitudes, conduct, and their remedies may vary from one culture to another. The paper is formed of five sections. Section one covers the notion and theories of politeness. Section Two deals with Politeness Strategies. Section three is devoted to Speech Acts as related to ‘Politeness’. Section Four tackles stylistic varieties as related to ‘Politeness’. Section Five tackles the shortcomings of the theory and draws a comparison between politeness and Impoliteness, reviewing models of Impoliteness to clarify the difference in the strategies used. The paper ends with the conclusions, followed by the bibliography.